Cascaded multioutput multilevel converter: modulation and operating limits - Ahmed S. Hussein (2022)
This article presents the modulation and operating limits of the modified cascaded multioutput multilevel converter. A phase-disposition pulsewidth modulation strategy is developed to apply the optimal state that leads to a minimized device switching. A Hamming distance-based cost function is adopted to evaluate the number of device transitions. The cost function is further modified to identify the optimal state from a number of feasible states. Moreover, the operating limits of the converter are analyzed for the safe and valid operation of the converter. Simulation and experiment results validate the theoretical analysis, and the converter is operational under a wide range of operation points. The proposed optimal state modulation strategy is shown to be effective in reducing the average device switching frequency.